Salinity extrusion and resilience of coastal aquaculture to the climatic changes in the southwest region of Bangladesh. Issue 3 (March 2023) - Bhowmik, Balai Chandra; Rima, Nazmun Naher; Gosh, Kamal; Hossain, Md Abul; Murray, Francis J.; Little, David C.; Mamun, Abdullah-Al
Abstract: The southwest coastal belt of Bangladesh is characterized by a fresh and saline water interaction which gives rise to a discrete inter-saline freshwater convergence zone (ICZ). Hydrology and farming along this transition zone is influenced by upstream and downstream abiotic factors including salinity intrusion and water flow. To better understand the changing geography of the transitional ICZ line and the relative influence of these hydrological events on farming therein, the recent study compared relative changes from 2010 to 2014 based on qualitative and quantitative survey work with 80 households of 4 villages (Shobna, Faltita, Badukhali and Rudaghora) from Khulna and Bagerhat district. Contrary to the conventional hotcake climate change induced salinity intrusion the study found a significant decrease in saltwater influx and increased freshwater volume in the ICZ villages, reflecting a seaward movement trend. Farmer perception shifted to low saline and freshwater in many areas where it was high saline and medium saline in 2010. The factual and perceived salinity were varied from 1 ± 0.44 to 2 ± 0.77 ppt in the studied villages. To confront the condition farmer diversified their farming pattern from single crop like either only shrimp or prawn culture to concurrent culture of shrimp-prawn, shrimp, prawn and rice with an increased production of (68-204 kg/ha), finfish (217-553 kg/ha) and dyke crop (92–800 kg/ha). Thus, affecting the socioeconomic condition of the farmer with an increase in average monthly income, reported for the better-off classes in 2014, ranged from 14, 300 to 51, 667 BDT and for the worse-off ranged from 5000 to 9900 BDT. In contrast, this average monthly income was 9500- 27, 000 for better-off and 3875 - 8600 for worse-off classes, reported in 2010. Besides, farming areas (average 17% for better-off and −0.5% for worse-off) and land leasing (average increment rate per ha 50%) also increased among the surveyed farmers, reported in 2014 compared to 2010. In addition, several adaptation strategies like unrefined salt use, change of water use, diversification through prawn, finfish and dyke crops along with traditional shrimp and overall land use change have a positive impact on farmer's economic and nutritional security as well as farming intensity. The study showed a unique attributes of salinity extrusion in micro-level of ICZ line where farmers intensified farming system with indigenous knowledge to secured their livelihoods.